Modelagem, identificação e projeto de controladores digitais para controle de um motor de corrente contínua - MACEDO, Gláucia Alves (2018)
The following work will present design strategies of digital controllers applied to speed regulation for a DC motor from WEG existing at the Laboratory of the Universidade Federal do Pará - Campus Tucuruí. Initially, experiments are performed and presented on parameters to identify the nature of engine speed control rotor axis as a function of applied voltage at the terminals of the motor armature. After defining the mathematical model that represents the dynamics of the DC motor, we conducted a brief study for design of digital controllers proportional-integral (PI), proportional-integral-derivative (PID) and RST. The strategy for PI and PID controllers is the method of the locus of the roots (LGR), which determines clusters of closed-loop system from the poles and zeros of open loop gain as a function of the system. A theoretical study on the structure and LGR RST is performed, then the controllers are designed according to predetermined specifications. The system is simulated with each controller, and the response is obtained for analysis and discussion of system performance from the designed controllers.